India-Africa enduring partnership : emerging areas of cooperation - Biswas, Aparajita (New Delhi : Gyan Publishing House, 2013)
Papers presented at an international seminar.
Section 1. Issues of Indian diaspora -- section 2. Non-traditional s ecurity issues -- section 3. India-Africa security issues -- section 4. India-Africa relations: expanding ties.
Includes bibliographical references and index.
Keywords: India -- Foreign relations -- Africa -- Congresses; Africa -- Foreign relations -- India -- Congresses; India -- Foreign economic relations -- Africa -- Congresses; Africa -- Foreign economic relations -- India -- Congresses